Gamification and work games: Examining consent and resistance among Uber drivers. (April 2022) - Vasudevan, Krishnan; Chan, Ngai Keung
In 2018, Uber released an overhauled mobile application for its independent contractor workforce, who had become increasingly dissatisfied by the lack of autonomy, transparency, and flexibility while working on the platform. Based on the gamification of work, the application linked individualized rewards with Uber's need to maintain a frictionless marketplace. However, as recent studies of gig economy have revealed, workers resist gamified algorithmic management by developing work games. Our findings, based upon analysis of driver accounts of using Uber's application, presents a typology of player modes and work games that drivers play. We identified two distinctive player modes, grinding and oppositional play, which, respectively, illustrate how drivers consent and resist gamification. We also describe several work games that Uber drivers play in resistance to Uber's gamification. This study contributes to the understanding of how the (re)design of worker-facing apps shape the power dynamics underpinning platform-initiated algorithmic governance and worker-initiated games.